Gambaran Burnout Pada Komunitas Pelari Rekreasional - Rifqi Rahmat Albari; Umi Anugerah Izzati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to describe the phenomenon of burnout among the recreational running community in Surabaya. The research employs a descriptive qualitative approach involving six participants, consisting of a community leader, two coaches, and three community members. Data were collected through in-depth interviews and participatory observation. The findings indicate that burnout manifests in three main forms that reflect the general dimensions of burnout: emotional exhaustion, withdrawal from community activities, and a decreased sense of personal accomplishment. These three aspects are interrelated and affect runners’ motivation, training consistency, and social involvement within the community. In conclusion, burnout among recreational runners is a complex psychological phenomenon influenced by activity demands, social pressure, and individuals’ perceptions of their own performance. Keywords: Burnout, Emotional Exhaustion, Sports Community, Recreational Runners’ Motivation